(untitled) (Performance, Religion, and Spirituality, 2024)
This essay considers the Meditations of Marcus Aurelius as a kind of philosophical performance manual. It argues that an appraisal of this text in terms of performance is one key way in which to understand the originality of the Meditations. Throughout much of the Meditations, Marcus surveys his own experience and the things occurring around him and attempts to create a kind of mental space (an “inner citadel”) from which to “correctly” perceive these experiences and events. But it is also clear that this “inner citadel” is a space that can only exist inasmuch as it is enacted, moment by moment. This essay follow’s Pierre Hadot’s claim that the Meditations offer a window into a set of “spiritual exercises” which would later be developed within a Christian context by Ignatius of Loyola. However, this essay argues that the Meditations differs considerably from the Ignatian Spiritual Exercises conceived thirteen centuries later, which envisions an ongoing dialogical relationship with a personal God rather than an inner dialogue set against the impersonal governance of Nature. It is this performative construction of the self, set in adversarial relation to the self-experiences of that self, that separates the Stoic spiritual experience from the Christian tradition that would eventually supplant it. In a contemporary secular context, however, it is very much this performative approach to aligning one’s identity with an all-encompassing world view, without encumbrance from organised religious structures, which ensures the continuing currency of the Meditations today.